Revisiting copper and zinc in end-stage renal disease patients - Sahab, Maha Abd; Al-Raheem, Basim Abd; Farouk, Khalid; Al-Hakeim, Hussein; Al-Sahab, Maha Abd (Pediatria Polska - Polish Journal of Paediatrics, 2024)
Numerous research projects have discovered how trace elements affect people with end-stage renal disease (ESRD). Thus, understanding the mechanism of action and the potential treatment options requires research into the chemical compounds that have an impact on the kidneys. Trace elements are components of metalloproteins and act as cofactors for numerous essential enzymes. Among the most important trace elements that affect renal function are zinc and copper. The newly published papers on changes in the effects of both trace element products in ESRD patients were studied, and the justifications gathered from earlier studies were compiled. This review’s findings suggest that changes in trace element levels worsen ESRD patients’ health condition by deepening kidney dysfunction, which has a negative impact on their health. The mechanism by which these effects occur is reviewed, and schemes were plotted in order to show a comprehensive view of the role of dysregulation of copper and zinc in ESRD patients.